2019
DOI: 10.1002/lt.25476
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Immunosuppression on Coagulation After Liver Transplantation

Abstract: Everolimus (EVR) is a mammalian target of rapamycin (mTOR) inhibitor commonly used for immunosuppression (IS) after liver transplantation (LT). However, there are concerns about whether mTOR inhibitors may move the hemostatic balance toward a higher likelihood of thrombosis. The present study aimed to investigate potential coagulation disorders after the administration of EVR. We evaluated 54 patients after conversion to an EVR‐based IS regimen (n = 26) and compared those patients with patients who were switch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“… 114 , 115 Several studies have reported that during the intraoperative and early postoperative phase, the plasma FVIII level usually increases. 114 , 115 Patients with end-stage liver disease undergoing liver transplantation consistently have higher FVIII levels than patients who survived had end stage liver disease but did not undergo treatments such as liver transplantation, 116 consistent with the severity of their liver disease and criteria for transplantation based on the severity of end-stage liver disease. Studies have shown that FVIII levels also are increased in children undergoing liver transplantation.…”
Section: Relevance Of Fviii In Cldmentioning
confidence: 99%
“… 114 , 115 Several studies have reported that during the intraoperative and early postoperative phase, the plasma FVIII level usually increases. 114 , 115 Patients with end-stage liver disease undergoing liver transplantation consistently have higher FVIII levels than patients who survived had end stage liver disease but did not undergo treatments such as liver transplantation, 116 consistent with the severity of their liver disease and criteria for transplantation based on the severity of end-stage liver disease. Studies have shown that FVIII levels also are increased in children undergoing liver transplantation.…”
Section: Relevance Of Fviii In Cldmentioning
confidence: 99%